Desempenho e eficiência econômica de novilhos Nelore submetidos a diferentes regimes alimentares - Filipe Lage Bicalho (2013)
It was evaluated the productive performance, effect of compensatory profit and the economic efficiency of different strategies of supplementation feed in the phase of recreates and grows fat of caves Nelore. The experiment was divided in three periods, dry, water and termination. Fifty and four calves with initial medium weight of 169.6 kg were divided in 8 handlings, being each handling a strategy of supplementation feed. In the dry period, the animals received energy supplement with medium consumption daily rate from 0.1% of the medium weight alive (PV) for the handlings TO, B, C, D and 0.2% of the PV for the handlings AND, F, G and H. In the period of the waters, the caves of the handlings TO, B, AND and F received energy supplement with medium consumption daily rate from 0.5% of the PV and the caves of the handlings C, D, G and H received mineral supplementation. In the period of termination, the animals of the handlings B, D, F and H received energy supplement with medium consumption daily rate from 1.4% of the PV and the animals of the handlings TO, C, AND and G were grown fat in confinement. There was an effect of compensatory profit between the strategies during the periods. The animals of the handlings that receivedsupplement 1.4% of the PV in the termination kept 70 days to more remained than the animals that were grown fat in confinement. All of the handlings were economically viable, however, the handling G presented the most greatest result of box, VPL and TIR being R$349,00; R$ R$252,10 e 2,45% respectively. There was an important effect ofcompensatory profit of the animals in the period of water and to supplementation of protein, energy and mineral to grass or in confinement reducing the age upon counting on the animals,being an economically viable alternative for output of bovine of cut.